Associação entre qualidade de vida e níveis de sintomas depressivos em pessoas idosas atendidas na atenção primária à saúde - Silva, Kamila Aiane Varela (2023)
The 2019 National Health Survey revealed that part of the population between 60 and 64 years old faces depression problems, highlighting the importance of directing attention and care to mental disorders in the elderly, which, therefore, can impact their quality of life at throughout the aging process. The objective of the study was to verify the association between quality of life and levels of depressive symptoms in elderly people treated in Primary Health Care (PHC). This is a quantitative, cross- sectional study carried out with elderly people treated in Primary Health Care units in Natal and Santa Cruz, in Rio Grande do Norte, Brazil, between 2017 and 2018. It was found that the study highlighted an association between quality of life and levels of depressive symptoms especially in areas related to Emotional (p=0.042), Functional (p=0.001), Physical (p=0.013), Mental Health (p=0.013) and General Health Status (p=0.013), as well as in the Physical Health dimension (p=0.019), characterizing the predominance of mild depression in the elderly. In conclusion, it is important to practice more effective approaches in the care and promotion of the integral well-being of the elderly, to improve the mental health of the elderly.